Budget impact and pharmacy costs with targeted use of oliceridine for postsurgical pain in patients at high risk of opioid-related adverse events. (19th May 2022) - Simpson, Kit N; Fossler, Michael J; Wase, Linda; Demitrack, Mark A; Wandstrat, Todd L
ABSTRACT: Background: Oliceridine, a new class of μ-opioid receptor agonist, may be associated with fewer opioid-related adverse events (ORAEs) due to its unique mechanism of action. Thus, it may provide a cost-effective alternative to conventional opioids such as morphine. Patients and Methods: Using a decision tree with a 24-hour time horizon, we calculated costs for medication and management of the three most common AEs (oxygen saturation <90%, vomiting, somnolence) following postoperative oliceridine or morphine in high-risk patients. Costs were enumerated as differences in cost of analgesics and resource utilization in the first 24 hours post-surgery. An economic model compared expected AEs and costs in a blended cohort where elderly/obese patients at higher risk for ORAEs received oliceridine while those presumed to be at lower risk received morphine with a cohort that received morphine alone. Results: In high-risk patients, use of oliceridine resulted in overall savings of 363, 944 (in 1, 000 patients). Implementing a targeted approach of oliceridine utilization in patients with high risk for ORAEs can save a typical hospital system 122, 296 in total cost of care. Conclusion: Use of oliceridine in postoperative care among patients at high risk provides a favorable health economic benefit compared to the use of morphine. PLAIN LANGUAGE SUMMARY: Oliceridine, a new class of opioid analgesics, administered directly into a vein, is a unique medication in that it provides pain relief equivalent to morphine and may have less costly side effects. It is given in a hospital/clinic or surgery center for the treatment of postoperative pain and can reduce costs compared to other opioid analgesics, possibly due to less side effects. An economic model was developed that compares morphine to oliceridine in patients more likely to experience sides effects due to traditional pain medications, comparing common side effects and pain relief following surgery. Although oliceridine costs more than morphine, in our economic model, the use of oliceridine resulted in cost savings (363, 944 US 2020 Dollars in 1, 000 patients), and a positive return of investment of over 7 times, when compared to morphine.